Blood flow-restricted strength training displays high functional and biological efficacy in women: a within-subject comparison with high-load strength training - Ellefsen, Stian; Hammarström, Daniel; Strand, Tor A.; Zacharoff, Erika; Whist, Jon E.; Rauk, Irene; Nygaard, Håvard; Vegge, Geir; Hanestadhaugen, Marita; Wernbom, Mathias; Cumming, Kristoffer T.; Rønning, Roar; et al. (American journal of physiology. Regulatory, integrative and comparative physiology, 2015)
Limited data exist on the efficacy of low-load blood flow-restricted strength training (BFR), as compared directly to heavy-load strength training (HST). Here, we show that 12 wk of twice-a-week unilateral BFR [30% of one repetition maximum (1RM) to exhaustion] and HST (6-10RM) of knee extensors provide similar increases in 1RM knee extension and cross-sectional area of distal parts of musculus quadriceps femoris in nine untrained women (age 22 ± 1 yr). The two protocols resulted in similar acute increases in serum levels of human growth hormone. On the cellular level, 12 wk of BFR and HST resulted in similar shifts in muscle fiber composition in musculus vastus lateralis, evident as increased MyHC2A proportions and decreased MyHC2X proportions. They also resulted in similar changes of the expression of 29 genes involved in skeletal muscle function, measured both in a rested state following 12 wk of training and subsequent to singular training sessions. Training had no effect on myonuclei proportions. Of particular interest, 1) gross adaptations to BFR and HST were greater in individuals with higher proportions of type 2 fibers, 2) both BFR and HST resulted in approximately four-fold increases in the expression of the novel exercise-responsive gene Syndecan-4, and 3) BFR provided lesser hypertrophy than HST in the proximal half of musculus quadriceps femoris and also in CSA peak , potentially being a consequence of pressure from the tourniquet utilized to achieve blood flow restriction. In conclusion, BFR and HST of knee extensors resulted in similar adaptations in functional, physiological, and cell biological parameters in untrained women.